Comparsion of Intubating Condition Using Three Different Doses of CIS-Atracurium Under General Anaesthesia - Kumar, Vasam Rajesh; Ninave, Sanjot; Singam, Amol P (International Journal of Psychosocial Rehabilitation, 2020)
Background: Cis-atracurium is the cis-cis isomer Methodology: Patients preoperative evaluation & airway assessment will be done and consent will taken before to surgery. 90 patient of ASA 1 & 2 in the age group 20 to 60 divided 3 group 30 each . Results: the three groups having hemodynamic stable. the higher doses having longer duration of action and better hemodynamic.Conclusion: Group C having longer duration of action and stable hemodyamics.